Indywidualny wywiad online - technika asynchroniczna = Individual online interview - asynchronous technique - Walentynowicz-Moryl, Katarzyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The purpose of this article is to characterize the method of individual online interview with particular emphasis on one of its techniques - asynchronous online interview. In the first part of the article, the author discusses the specificity of conducting personal online interviews, which results primarily from the fact that they are conducted with the use of computer-mediated communication. The author then points out the division of individual online interviews into synchronous and asynchronous online interviews due to the time of their conduct.
Keywords: metody jakościowe; indywidualny wywiad online; asynchroniczny wywiad online; qualitative methods; individual online interview; asynchronous online interview